COLLECTIVE CASE STUDIES ON ETHNO-MEDICINE AND HEALTHCARE SYSTEMS AMIDST GLOBAL NATIVE FOLKS - Sharmistha Aich (ADISAM Publisher, 2022)
Anthropologically, ethnicity delineates people who are categorized according to their ethnolinguistic languages or grouped in accordance to their explicit dialects, castes, cultures, traditions, customs, and admixture of various clans. The intermarriages among these groups gave rise to diversified miscellaneous ethnic groups all over the world having their own ethnicity, varied cultures, traditions, and ethnomedicines. Human societies have their own conceptualization of health and diseases which are accompanied by indigenous health practices and mechanisms, based on magico-religious concepts that unearthed the medicinal values of plants and animals. This process eventually lead to the success of ethnomedicine and its contribution to Medical Anthropological Knowledge. The term ethnomedicine, which means to heal from within, is a deliberate effort to grasp, recommend, educate, exercise, and execute the various Traditional Medicines in different ethnic groups. Ethnomedicine is distinguished and practiced exclusively in primitive societies which have a common ancestry, similar clan, caste, geographical location, food pattern, cultures, traditions, and practices. Several thousand years ago (in antiquity) with the awareness of various ailments and diseases arose, numerous methods for treatment to cure innumerable diseases slowly and consecutive emerged in human society. This popularised the notion of ethnomedicine which preached that not only the physical body but also mental stability are paramount to having a disease-free life. Indian Ayurveda and Yoga, Traditional Chinese Medicine (TCM), African Traditional Medicine (ATM), and Unani Medicine of Mughal India, are a few examples of ethnomedicines. Medical Anthropologists unwrapped and divulged the ethnomedicinal facts, thousands of years that emerged from common descent and were practiced in indigenous societies of China, Africa, and India. The present article reflects the composition of preferred Case Studies in Medical Anthropology and ethnomedicine of Tribals of India, Glimpses of African Traditional Medicine (ATM), and Unani Methods to cure disease in the Indian Sub-continent. The study concluded the importance of ethnomedicine among Indians by stating that in 2022, World Health Organization (WHO) and the Government of India signed an agreement in Gujarat, India, to develop an institute for ‘The Global Centre for Traditional Medicine’ which attempts to portray ethnomedicine in collaboration with Science and Technology for the betterment of human being